DA'WAH STRATEGY BY THE ASSEMBLY OF MUJAHADAH SHALAWAT HUBBUSYAFA'AT IN OVERCOMING THE CRISIS OF MODERN SOCIETY - Muhyiddin, Ahmad Shofi (Jurnal Al-Hikmah: Jurnal Dakwah, 2023)
Modernity with all the advances in science and technology has dominated human life and left problems and negative influences, especially those related to human psychological conditions such as mental, spiritual and spiritual life. As a result, various kinds of social crises emerge, structural crises, moral crises, spiritual crises whose roots are the problem of the meaning of human life itself. In the end it creates mental anxiety, such as stress, frustration, depression, alienation, even dehumanization. The Mujahadah Shalawat Hubbussyafa'at Assembly exists as a fortress and medicine for diseases caused by modernity. The Mujahadah Shalawat Hubbussyafa'at Assembly through mujahadah-shalawat activities in the study of da'wah science can be used as a strategy based on spirituality in the Modern era or in al-Bayānūnī's language it is called a sentimental strategy (al-manhaj al-'āṭifi). In addition, in its implementation, this activity also contains several kinds of sentimental strategies (al-manhaj al-'āṭifi) in overcoming the problems of modernism, including: provision of guidance, the unifier of the Islamic ummah or ukhuwah Islamiyah, preaching that is not burdensome and giving motivation. Not only that, the activities of the Mujahadah Shalawat Hubbussyafa'at Assembly are also an external-institutional da'wah strategy.